Metaphors are physical and abstract: ERPs to metaphorically modified nouns resemble ERPs to abstract language - Forgács, Bálint; Bardolph, Megan D.; Amsel, Ben D.; DeLong, Katherine A.; Kutas, Marta (Frontiers in Human Neuroscience, 2015)
Metaphorical expressions very often involve words referring to physical entities and experiences. Yet, figures of speech such as metaphors are not intended to be understood literally, word-by-word. We used event-related brain potentials (ERPs) to determine whether metaphorical expressions are processed more like physical or more like abstract expressions. To this end, novel adjective-noun word pairs were presented visually in three conditions: (1) Physical, easy to experience with the senses (e.g., “printed schedule”); (2) Abstract, difficult to experience with the senses (e.g., “conditional schedule”); and (3) novel Metaphorical, expressions with a physical adjective, but a figurative meaning (e.g., “thin schedule”). We replicated the N400 lexical concreteness effect for concrete versus abstract adjectives. In order to increase the sensitivity of the concreteness manipulation on the expressions, we divided each condition into high and low groups according to rated concreteness. Mirroring the adjective result, we observed a N400 concreteness effect at the noun for physical expressions with high concreteness ratings versus abstract expressions with low concreteness ratings, even though the nouns per se did not differ in lexical concreteness. Paradoxically, the N400 to nouns in the metaphorical expressions was indistinguishable from that to nouns in the literal abstract expressions, but only for the more concrete subgroup of metaphors; the N400 to the less concrete subgroup of metaphors patterned with that to nouns in the literal concrete expressions. In sum, we not only find evidence for conceptual concreteness separable from lexical concreteness but also that the processing of metaphorical expressions is not driven strictly by either lexical or conceptual concreteness.